Epstein‐Barr virus‐encoded miR‐BART6‐3p inhibits cancer cell proliferation through the LOC553103‐STMN1 axis. Issue 6 (18th April 2020) - Wang, Dan; Zeng, Zhaoyang; Zhang, Shanshan; Xiong, Fang; He, Baoyu; Wu, Yingfen; Li, Weimin; Tang, Le; Wei, Fang; Xiang, Bo; Li, Zheng; Zhou, Yanhong; et al.
Abstract: Epstein‐Barr virus (EBV) is a tumorigenic virus that can cause various human malignancies such as nasopharyngeal carcinoma (NPC) and gastric cancer (GC). EBV encodes 44 mature micro (mi)RNAs, mostly exhibiting oncogenic properties and promoting cancer progression. However, we have previously found that one EBV‐encoded miRNA, namely EBV‐miR‐BART6‐3p, acts as a tumor suppressor by inhibiting metastasis and invasion. Here, we report that EBV‐miR‐BART6‐3p inhibits the proliferation of EBV‐associated cancers, NPC, and GC, by targeting and downregulating a long non‐coding RNA (lncRNA), LOC553103. Through proteomics analysis, we determined that stathmin (STMN1) is affected by EBV‐miR‐BART6‐3p and LOC553103. Further, via RNA immunoprecipitation and luciferase reporter assay, we confirmed that LOC553103 directly binds and stabilizes the 3′UTR region of STMN1 mRNA. These results indicate that the EBV‐miR‐BART6‐3p/LOC553103/STMN1 axis regulates the expression of cell cycle‐associated proteins, which then inhibit EBV‐associated tumor cell proliferation. These findings provide potential targets or strategies for novel EBV‐related cancer treatments, as well as contributes new insights into the understanding of EBV infection‐related carcinogenesis.